Improving Firm’s Economic and Environmental Performance Through the Sustainable and Innovative Environment: Evidence From an Emerging Economy - Ahmad, Naveed; Scholz, Miklas; AlDhaen, Esra; Ullah, Zia; Scholz, Philippa (Frontiers in Psychology, 2021)
Businesses in the present era are dealing with a complex and unprecedented brew of social, environmental, and technological trends. This requires sophisticated, sustainability-based management. Yet organizations are often reluctant to place sustainability core to their business strategies with the mistaken belief that the costs associated with environmental investments outweigh the benefits. The Global Climate Risk Index has placed Pakistan on 5th position in the list of nations, most susceptible to climate change in its recent report. Pakistan lost the lives of 9,989 people, incurred economic losses of $ 3.8 billion, and faced 152 shocking climates between 1999 and 2018. Based on this information, it is established that Pakistan's susceptibility to climate change is growing unprecedentedly and industrial pollution is one of the biggest contributors in this respect. The country needs to take emergency measures to address this issue. With this background, the present study aims to investigate the impact of environmental sustainability on environmental and economic performance with the mediating effect of environmental innovation in the manufacturing sector of Pakistan. The results show that environmental sustainability is a significant predictor of environmental and economic performance and environmental innovation mediates this relationship. The findings of the present study provide better insights to policymakers to address the environmental degradation, resulting from industrial pollution